Effects of Operation Conditions on Antioxidant and Iron Chelating Activity of Chemical Hydrolysates from Red Tilapia (Oreochromis sp.) Scales (2018)
ABSTRACT: The aim of this study was to optimize the alkaline hydrolysis to extract protein from RTS with antioxidant and iron chelating activity. Red Tilapia (Oreochromis sp.) scales (RTS) have essential protein contents; therefore, those represent an opportunity to obtain hydrolysates, which may present biological activities of interest. For the extraction of the protein, it is possible to use chemical methods such as alkaline hydrolysis. The factors of central composite design (DOE) were NaOH concentration (0.5 to 2M), temperature (40 to 60°C) and percentage of scales (2.5 to 7.5%). The response variables were: protein (g/L), antioxidant capacity (ABTS and FRAP) and percentage of iron chelating activity (ICH). The hydrolysis time was evaluated in 2, 4 and 8 h in a 500 mL reactor with constant stirring. It was possible to obtain significant models for the variables assessed and those showed that with high levels of temperature, NaOH concentration and substrate concentration get a higher concentration of soluble protein without affecting the biological activities evaluated. The quantity of the protein obtained for the optimal DOE conditions was 20 g/L, with an extraction yield of 98%. The best time to get proteins with bioactivity was 2 h. This study evidenced the obtainment of protein hydrolysates from RTS with antioxidant and iron chelating activity using alkaline hydrolysis.